2020
DOI: 10.1111/ped.14036
|View full text |Cite
|
Sign up to set email alerts
|

Nonosmotic secretion of arginine vasopressin and salt loss in hyponatremia in Kawasaki disease

Abstract: Background The precise mechanism of hyponatremia in Kawasaki disease (KD) remains elusive because assessment of volume status based on serial changes in body weight is lacking in previous reports. Methods Seventeen patients who were diagnosed with KD and hyponatremia (serum sodium levels <135 mmol/L) were analyzed. Volume status was assessed based on serial changes in body weight. Plasma arginine vasopressin (ADH), urine electrolytes, and serum cytokine levels were measured on diagnosis of hyponatremia. An inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…In this issue of the Journal, Miura et al showed that, in most Kawasaki disease patients, hypotonic dehydration was unlikely to be a cause of hyponatremia. And they report that hyponatremia in KD is euvolemic or hypervolemic and is associated with nonosmotic secretion of ADH and salt loss in the majority of patients . From their reports, it is considered that large amounts of fluid replacement are not necessary for correction of hyponatremia in KD.…”
mentioning
confidence: 99%
“…In this issue of the Journal, Miura et al showed that, in most Kawasaki disease patients, hypotonic dehydration was unlikely to be a cause of hyponatremia. And they report that hyponatremia in KD is euvolemic or hypervolemic and is associated with nonosmotic secretion of ADH and salt loss in the majority of patients . From their reports, it is considered that large amounts of fluid replacement are not necessary for correction of hyponatremia in KD.…”
mentioning
confidence: 99%
“…Hyponatremia can be experienced in a variety of in ammatory diseases [15]. KD patients in the acute phase frequently have hyponatremia [16][17][18][19]. A national survey on KD in Japan showed that almost 60% patients had serum Na levels below 134 mEq/mL [20].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies on the overall incidence of hyponatremia in children, with wide variation in the reported incidence rates in hospitalized children. The heterogeneity in the scientific literature is due to some factors, such as cut-off values of plasma sodium level [6], scope of patient care (general ward or intensive care) [1], process of hospitalization (emergency, elective, medical, or surgical) [7,8], and studies limited to specific clinical pathologies, such as gastroenteritis [9], bronchiolitis [9], pneumonia [10], meningitis [11], pyelonephritis [9], and others [12,13]. Therefore, it is difficult to validate the incidence of hyponatremia in hospitalized children on a general pediatric ward from published data.…”
Section: Introductionmentioning
confidence: 99%